Stewardship applied to antipsychotics: Development of an antipsychotic stewardship program in inpatient settings for monitoring and optimizing outcomes - Gillian Gonzales, PharmD; Kari Tornes, PharmD; Stephen R. Saklad, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2022)
Antipsychotic (AP) medications are prescribed for various psychiatric diagnoses that require routine monitoring to ensure optimal use, effectiveness, adherence, and for potentially severe adverse effects. There is currently no comprehensive protocol for institutional supervision of prescribing and monitoring AP. Antibiotics (ABX) are commonly associated with stewardship programs aimed at optimizing use and mitigating harm. These programs have proven to result in positive outcomes in both safety and efficacy parameters for numerous institutions. Given that AP are also associated with significant adverse effects and often misused, the concept of stewardship can be applied to this class of agents to optimize their use and improve overall patient outcomes. The objective of this paper is to provide guidance for the implementation of antipsychotic stewardship programs (APSP) in the inpatient setting. The development of this APSP was designed based on ABX stewardship programs and the Centers for Disease Control and Prevention, Agency for Healthcare Research and Quality, and the American Psychiatric Association practice guidelines on the treatment of patients with schizophrenia. In conclusion, APSPs have the potential to enhance and standardize institutional supervision of prescribing and monitoring practices of AP, leading to improved clinical outcomes and the reduction of adverse effects. APSP teams should be multidisciplinary, consisting of clinicians and administrators, working in conjunction with patients and patient advocates to design individualized recovery plans that consider the individual patient's history and desired outcomes. Monitoring, stewardship interventions, and outcomes should be documented on both an individual and deidentified institutional basis, analyzed, and summarized periodically as measures for quality improvement.